Best Answer

2j+1/j+5 = 1

Multiply all terms by j+5 to eliminate the fraction:

2j+1 = j+5

2j-j = 5-1

j = 4

Q: How do you solve 2j plus 1 divided by j plus 5 equals 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3j-13=11+2j 3j-13-2j = 11+2j-2 j-13 = 11 j-13 +13 = 11 + 13 = 24 so j = 24

It is also x = 5 8zx + 5 = 2j + 3 → 8zx + 2 = 2j → 4zx + 1 = j Which is the first equation, which has a solution x = 5.

J does not equal a value since you didn't provide an equation; there's no equal sign nor a "right side." You have provided an expression that can be simplified but nothing more. Unfortunately, both equation and expression begin with the letter E in English which, I believe, can lead to the confusion. Now if 4j-24-6j equals 120 then we have something to work with! So then -24-2j equals 120 and -2j equals 144 and, finally, j equals -72. I hope this helps.

The magnitude of (i + 2j) is sqrt(5). The magnitude of your new vector is 2. If both vectors are in the same direction, then each component of one vector is in the same ratio to the corresponding component of the other one. The components of the known vector are 1 and 2, and its magnitude is sqrt(5). The magnitude of the new one is 2/sqrt(5) times the magnitude of the old one. So its x-component is 2/sqrt(5) times i, and its y-component is 2/sqrt(5) times 2j. The new vector is [ (2/sqrt(5))i + (4/sqrt(5))j ]. Since the components of both vectors are proportional, they're in the same direction.

Consider prime numbers p1, p2 greater than 2. Since p1 and p2 are prime and greater than 2, they are both necessarily odd. Hence, they are of the form: p1 = 2k+1, p2 = 2j+1, where j and k are positive integers. Their sum is then: p1+p2 = (2k+1)+(2j+1) = 2k+2j+2 = 2 (k+j+1). So 2 divides their sum, hence the sum can't be prime

Related questions

3j-13=11+2j 3j-13-2j = 11+2j-2 j-13 = 11 j-13 +13 = 11 + 13 = 24 so j = 24

36.64

It is also x = 5 8zx + 5 = 2j + 3 → 8zx + 2 = 2j → 4zx + 1 = j Which is the first equation, which has a solution x = 5.

3-2j.

2 + 5j

Re-write it properly first, in all-algebraic language: ' 7 + 8j + 7 -2j ' Now put like terms together: ' 7 + 7 +8j - 2j ' Then simplify by doing the arithmetic: ' 14 + 6j. ' And there you are!

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".

J does not equal a value since you didn't provide an equation; there's no equal sign nor a "right side." You have provided an expression that can be simplified but nothing more. Unfortunately, both equation and expression begin with the letter E in English which, I believe, can lead to the confusion. Now if 4j-24-6j equals 120 then we have something to work with! So then -24-2j equals 120 and -2j equals 144 and, finally, j equals -72. I hope this helps.

3i+2j)*(2i-3j)=0 bcz dot product is zero.

It is (2j/5)2

243 mph

Chaparral 2J